Trustworthy-looking face meets brown eyes - Kleisner, Karel; Priplatova, Lenka; Frost, Peter; Flegr, Jaroslav (PloS one, 2013)
We tested whether eye color influences perception of trustworthiness. Facial photographs of 40 female and 40 male students were rated for perceived trustworthiness. Eye color had a significant effect, the brown-eyed faces being perceived as more trustworthy than the blue-eyed ones. Geometric morphometrics, however, revealed significant correlations between eye color and face shape. Thus, face shape likewise had a significant effect on perceived trustworthiness but only for male faces, the effect for female faces not being significant. To determine whether perception of trustworthiness was being influenced primarily by eye color or by face shape, we recolored the eyes on the same male facial photos and repeated the test procedure. Eye color now had no effect on perceived trustworthiness. We concluded that although the brown-eyed faces were perceived as more trustworthy than the blue-eyed ones, it was not brown eye color per se that caused the stronger perception of trustworthiness but rather the facial features associated with brown eyes.
Keywords: barva očí; Young Adult; Male; mladý dospělý; Form Perception; Adult; dospělí; Trust; mužské pohlaví; obličej; Eye Color; vnímání tvaru; lidé; ženské pohlaví; Humans; důvěra; Face; Female; lidé středního věku; Middle Aged